High light stress induces H2O2 production and accelerates fruit ripening in tomato - Steelheart Molina, Maria Charlotte (2022)
Increased synthesis of H2O2 is observed during the initiation of fruit ripening. However, its association with plant cell processes triggering the maturation of fruit has not yet been demonstrated. The aim of this work is to investigate whether H2O2 participates in the tomato ripening process and particularly through its association with the ethylene signaling pathway. The experiments were carried out with two ethyl methanesulfonate mutant lines of Micro-Tom tomato deficient in GDP-L-galactose phosphorylase activity and displaying lower ascorbic acid content than the corresponding parental genotype (i.e. wild type). Plants were subjected to a high irradiance (HI) treatment to stimulate H2O2 synthesis. HI treatment enhanced H2O2 production and reduced the timing of fruit ripening in both mutants and wild-type fruits. These results could be linked to an increase of the expression of H2O2-related genes and changes in the expression of ethylene-related genes. The fruit H2O2 production increased or decreased after applying the treatments that induced ethylene synthesis or blocked its action, respectively. The results presented in this work give an evidence of the association of redox and hormonal components during fruit ripening in which H2O2 participates downstream in the events regulated by ethylene.